Public freedom - Villa, Dana Richard (Princeton University Press, 2008)
"In Public Freedom, renowned political theorist Dana Villa argues that political freedom is essential to both the preservation of constitutional government and the very substance of American democracy itself. Through intense close readings of theorists such as Hegel, Tocqueville, Mill, Adorno, Arendt, and Foucault, Villa diagnoses the key causes of our democratic discontent and offers solutions to preserve at least some of our democratic hopes. He demonstrates how Americans' preoccupation with a market-based conception of freedom - that is, the personal freedom to choose among different material, moral, and vocational goods - has led to the gradual erosion of meaningful public participation in politics as well as diminished interest in the health of the public realm itself. Villa critically examines, among other topics, the promise and limits of civil society and associational life as sources of democratic renewal; the effects of mass media on the public arena; and the problematic but still necessary ideas of civic competence and democratic maturity."--Jacket